2018
DOI: 10.3329/kyamcj.v9i1.36617
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance pattern in pseudomonas aeruginosa isolated from a private Medical College Hospital

Abstract: Background: Pseudomonas aeruginosa is an aerobic, motile, gram negative rod that belongs to the family, Pseudomonadaceae. They are often multidrug resistant due to intrinsic and acquired determinants. Continued emergence of resistance among P. aeruginosa to common antimicrobial drugs has been reported world-wide.Objectives: This study investigated the antimicrobial resistance as well as susceptibility patterns of isolates of P. aeruginosa in clinical specimens.Materials & Methods: One hundred and thirty-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
2
8
1
Order By: Relevance
“…Studies in Ethiopia and India have noted P. aureginosa to be highly resistant to many antibiotics [39,40]. Therefore, judicious and rational treatment prescription by physicians to limit further the spread of antimicrobial resistance among the P. aeruginosa, as recommended by Siddiqua et al [38] is highly supported by this study.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Studies in Ethiopia and India have noted P. aureginosa to be highly resistant to many antibiotics [39,40]. Therefore, judicious and rational treatment prescription by physicians to limit further the spread of antimicrobial resistance among the P. aeruginosa, as recommended by Siddiqua et al [38] is highly supported by this study.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, Yayan et al [37] have reported an elevated resistance of P. aeruginosa and MDR P. aeruginosa for cefepime in Germany. In a study by Siddiqua et al [38] using P. aeruginosa from clinical specimens (wound, pus and urine), the isolated pathogens showed resistance to cefepime, ceftriaxone, cefotaxime and gentamicin from 47% to 88%. All the isolates from their study were comparatively better susceptible to meropenem, similar to what is observed in this study with 79% susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas is an aerobic, motile, Gram-negative bacterium and has been implicated in diverse healthcare associated infections (HCAIs) such as pneumonia, urinary tract infection, skin and soft-tissue infections, in severe burns and in infections among immunocompromised individuals12345. Multidrug-resistant Pseudomonas is especially associated with increased mortality because no adequate therapeutic options exist678.…”
mentioning
confidence: 99%
“…A total of fifteen articles published in English, between the period of 2010 and 2020 were identified and reviewed, nine articles were prospective studies (Siddiqua et al, 2018;Farooq et al, 2019;Ahmadi et al, 2016;Rustini et al, 2017;Senthamarai, 2014;Farhan et al, 2019;Ahmed et al, 2019;Al-Marzoqi and Al Taee, 2013;Khan and Faiz, 2016), four were descriptive cross sectional studies (Pokharel et al, 2019;Karami et al, 2020;Mahfoud et al, 2015;Alhusseini et al, 2019), one systemic review and meta-analysis study (Acar et al, 2019) and one retrospective study (Al-Tawfiq et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This study focused mainly on the resistance pattern of P. aeruginosa against different drugs in different countries. It was observed that the highest resistance rate was against Cefuroxime in Bangladesh (Siddiqua et al, 2018), Ceftriaxone in Indonesia (Rustini et al, 2017), Imipenem in Pakistan (Farooq et al, 2019), Ampicillin (Ahmadi et al, 2016) and Ticarcillin/Clavulanic Acid (Karami et al, 2020) in Iran, Co-Trimoxazole in Nepal (Pokharel et al, 2019), Ceftazidime in India and Egypt (Senthamarai, 2014;Farhan et al, 2019), Cefepime in Qatar (Ahmed et al, 2019), Amoxicillin/Clavulanic Acid in Syria (Mahfoud et al, 2015), Penicillin and Amoxicillin/Clavulanic Acid in Iraq (Alhusseini et al, 2019), Aztreonam in Turkey (Acar et al, 2019) and Meropenem (Khan and Faiz, 2016), Ciprofloxacin followed by Meropenem and Imipenem (Al-Tawfiq et al, 2020) then both Carbapenems (Al-Tawfiq et al, 2020) in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%